UTILIZATION OF SOCIAL MEDIA-BASED HYPERLOCAL MARKETING TO INCREASE BRAND AWARENESS OF MSMEs IN DAUH PURI KAUH VILLAGE - Ni Putu Maharani Artika Devi; Kadek Devi Kalfika Anggria Wardani; Anak Agung Ngurah Eddy Supriyadinata Gorda; Dewa Ayu Putu Adhiya Garini Putri (LPPM Universitas Flores, 2026)
This community service program was initiated in response to the limited utilization of social media as a promotional tool among MSMEs at Pasar Banjar Sumuh, Dauh Puri Kauh Village, despite strong local market potential. The program aimed to enhance brand awareness and digital competencies of MSME actors through the implementation of social media–based hyperlocal marketing strategies. A total of 10 MSMEs were involved in the initial assessment, with 8 businesses (80%) lacking active business accounts and location-based promotional knowledge. The implementation stages included field surveys, interviews, content planning, branding video production, banner installation, and publication through Instagram Reels and TikTok. Evaluation was conducted using pre-test and post-test Likert-scale questionnaires, social media engagement metrics, and sales data analysis. The results indicated a 65% increase in digital marketing understanding among participants after mentoring. The published promotional video generated 1,311 views, 73 likes, 8 shares, and 7 comments. In addition, the average number of daily customers increased from 25 to 35 (a 40% increase). The findings demonstrate that community- and location-based video content effectively strengthens brand identity and improves local consumer engagement. In conclusion, hyperlocal marketing strategies significantly enhanced MSME visibility, digital competence, and brand awareness at the local level. Follow-up actions include continuous mentoring, advanced content performance analysis training, and collaborative digital promotion among MSMEs and village stakeholders to ensure sustainability.